2020
DOI: 10.21037/apm-20-1662
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on lung cancer patients

Abstract: Background: The coronavirus disease poses an unprecedented challenge to health and epidemic prevention system, especially the healthcare of patients with cancer. We sought to study the impact of COVID-19 on lung cancer patients in our center. Methods:We initiated a retrospectively study to analyze the impact of COVID-19 on lung cancer patients in our center, who were accepted for routine anticancer treatment before the epidemic and planned to return to hospital in January and February of 2020.Results: A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 4 publications
1
25
0
Order By: Relevance
“…55 While data demonstrating the effect of COVID-19 specifically on lung cancer research is scant, several studies show that cancer research in general has been compromised. [56][57][58][59][60][61][62][63] Cancer clinical trials have been at the focus of these studies, but it is essential to highlight that translational and observational studies have also been affected. 57 The mechanisms by which research has been compromised include decreased funding, operational concerns with tissue collection and biobanking, holds on clinical trials, reduced workforce, and reduced networking opportunities for international collaborations.…”
Section: Impact Of Covid-19 Pandemic On Lung Cancer Researchmentioning
confidence: 99%
“…55 While data demonstrating the effect of COVID-19 specifically on lung cancer research is scant, several studies show that cancer research in general has been compromised. [56][57][58][59][60][61][62][63] Cancer clinical trials have been at the focus of these studies, but it is essential to highlight that translational and observational studies have also been affected. 57 The mechanisms by which research has been compromised include decreased funding, operational concerns with tissue collection and biobanking, holds on clinical trials, reduced workforce, and reduced networking opportunities for international collaborations.…”
Section: Impact Of Covid-19 Pandemic On Lung Cancer Researchmentioning
confidence: 99%
“…Sha et al first investigated the impact of COVID-19 on non-COVID-19 lung cancer patients during the pandemic. The study demonstrated the significant impact of the COVID-19 crisis on oncological care, indicating that treatment decisions, follow-up and psycho-oncological support need to be changed during pandemic [19]. A study done by a Korean group analyzed the impact of COVID-19 on lung cancer diagnosis in Korea, where lung cancer incidence continues to rise, and they found that the proportion of patients with advanced non-small-cell lung carcinoma (NSCLC) increased during the COVID-19 pandemic [20].…”
Section: The Mortality Of Lung Cancer Patients May Increase Once Infementioning
confidence: 97%
“…Since the outbreak of 2019 novel coronavirus disease (COV-ID- 19) induced by a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the pandemic has become a global catastrophe resulting in overwhelming impacts on human life [1,2]. In an effort to prevent the spread of the COVID-19, various activities and academic events including cancer medicare, research and academic conferences have been highly interrupted [3].…”
Section: Introductionmentioning
confidence: 99%
“…During COVID-19 pandemic anxiety of oncologic patients has grown and often resulted in requested therapy delays. With the delays in therapy, the risk of tumour progression rises and threatens the life safety of patients [38,39].…”
Section: Lung Cancer Management During Pandemicmentioning
confidence: 99%